Patient-driven research priorities for patient-centered measurement - A. Fuchsia Howard; Linda Warner; Lena Cuthbertson; Richard Sawatzky (BMC, 2024)
Abstract Background Patient-centred measurement (PCM) emphasizes a holistic approach wherein the voices of patients are reflected in the standardized use of patient-reported outcome and experience measures and are represented throughout the continuum of measurement activities. Given the challenges of routinely integrating patient self-reports into clinical care decisions, the perspectives of all healthcare system stakeholders, especially patients, is necessary to advance the science of PCM. The purpose of the analysis we report on here was to identify patient-driven research priorities for advancing the science of PCM. Methods We analyzed data from seven focus groups that were conducted across British Columbia, Canada and that included a total of 73 patients, using qualitative inductive analysis and constant comparative methods. Results We found that the patients conveyed a desire for PCM to contribute to healthcare decisions, specifically that their individual healthcare needs and related priorities as they see them are always front and centre, guiding all healthcare interactions. The patients' commentaries highlighted intersecting priorities for research on advancing the science of PCM that would help transform care by (1) enhancing the patient-provider relationship, (2) giving voice to patients' stories, (3) addressing inclusivity, (4) ensuring psychological safety, (5) improving healthcare services and systems to better meet patient needs, and (6) bolstering healthcare system accountability. Conclusions These priorities provide direction for future research efforts that would be positioned to make progress towards better health, better care, and better use of resources for individuals and for society.